Quantitative analysis of the intensity distribution of optical rogue waves - Rácz, Éva; Spasibko, Kirill; Manceau, Mathieu; Ruppert, László; Chekhova, Maria V.; Filip, Radim (Communications Physics, 2024)
The field of optical rogue waves is a rapidly expanding topic with a focus on explaining their emergence. To complement this research, instead of providing a microscopic model that generates extreme events, we concentrate on a general quantitative description of the observed behavior. We explore two complementary top-down approaches to estimating the exponent describing the power-law decaying distribution of optical rogue waves observed in supercontinuum generated in a single-mode fiber in the normal-dispersion regime by applying a highly fluctuating pump. The two distinct approaches provide consistent results, outperforming the standard Hill estimator. Further analysis of the distributions reveals the breakdown of power-law behavior due to pump depletion and detector saturation. Either of our methods is adaptable to analyze extreme-intensity events from arbitrary experimental data.
CRIS-Team Scopus Importer:2024-04-26